Human-Wildlife Conflict: The Case of Arjo Dhidhessa Sugar Factory and Its Surrounding, Western Ethiopia (Research and Social Study Institute, 2021)
Human-wildlife conflict (HWC) occurs in various forms throughout the world, with a greater influence in developing countries. This is due to fast increasing human populations and increased subsistence agriculture, which reduces wildlife habitat and increases human-wildlife interactions. Wild animals fight for resources with humans in the Arjo Dhidhesa Sugar Factory in Western Ethiopia, and they are in conflict with each other. As a result, this research was carried out to determine the reasons of HWC, as well as the mammals responsible for them. From August 2017 to March 2018, researchers utilized questioner and interview approaches to examine community perceptions toward wildlife and overall cthe result showed that a total of 99.034 sugarcane stalk damage events were registered in all three sample sites both during the dry and wet seasons. Wildlife consumed 46,468 sugarcane stalks during the rainy season, while 52,566 stalks were consumed during the dry season, with the documented damage event varying greatly from site to site. Hippopotamus, Anubis baboon, Warthog, Bush pig, and Buffalo were the most affected by HWC, with agricultural loss occurring throughout both wet and dry seasons. During the wet season, Hippopotamus 16,133 stalks per ha were the most damaged, followed by Anubis baboon 12,484 stalks per ha. Buffalo 5,083 and Bush pig 3,931 stalk per ha did the least damage, placing fourth and fifth, respectively. During dry seasons, Anubis baboon caused the most sugarcane stalk damage (16, 898 stalks per hectare), followed by hippopotamus (16,533 stalks per ha). During both the wet (t = 4.08, DF = 4, P< 0.05) and dry seasons (t =3.73, DF = 4, P< 0.05), there was a significant difference in the damages caused by mentioned fauna. According to the findings, about 67.9% and 25.2 % of all respondents said that HWC expressed itself in crop destruction and livestock predation, respectively. Habitat damage, agricultural development, a lack of feed, and a rise in the population of wild animals are among the explanations cited by respondents. Some of the key crop raider mitigation strategies revealed in this study that were adopted by the investment community and local communities include hanging dead animal parts, habitat disturbance, keeping animals alive by tying them to the side of field, and mass murdering wildlife. These practices are one of the main causes of the extinction of wildlife, making conservation even more challenging. There are currently many human activities in the field of science, which has resulted in many HWCs. As a result, investment decisions should be made based on strong and viable domain choices both commercial and environmental, as well as promoting natural tourism as a viable option for education and conservation education.